1997
DOI: 10.1124/mol.51.6.1007
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Roles of Muscarinic Acetylcholine Receptors on T Cell Antigen Receptor/CD3 Complex-Mediated Interleukin-2 Production in Human Peripheral Blood Lymphocytes

Abstract: It is known that there are some bidirectional interactions between the nervous and the immune systems via neurotransmitters and cytokines. To clarify whether any neurotransmitters modulate lymphocyte functions, we examined the effects of oxotremorine-M (Oxo-M) on interleukin-2 (IL-2) production in human peripheral blood lymphocytes by using enzyme-linked immunosorbent assays, Northern blot analyses, reverse transcriptase-polymerase chain reaction, and fluorescence-activated cell sorter. Pretreatment of cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…50 The current data confirm and extend on previous pharmacological 26,27 and mRNA expression studies that suggested the existence of multiple muscarinic receptors on blood lymphocytes. 33,63,51,52 While mRNA for m3, m4, and m5 receptors has been reported in mononuclear cells, the additional detection of m3 and m4 mRNA in neutrophils and stromal cells remains a novel finding. Acetylcholine synthesis and release from T-lymphocytes via muscarinic receptors have been documented; 53 however, such stimulation of muscarinic receptors on stromal cells by direct contact through adhesion molecules remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The current data confirm and extend on previous pharmacological 26,27 and mRNA expression studies that suggested the existence of multiple muscarinic receptors on blood lymphocytes. 33,63,51,52 While mRNA for m3, m4, and m5 receptors has been reported in mononuclear cells, the additional detection of m3 and m4 mRNA in neutrophils and stromal cells remains a novel finding. Acetylcholine synthesis and release from T-lymphocytes via muscarinic receptors have been documented; 53 however, such stimulation of muscarinic receptors on stromal cells by direct contact through adhesion molecules remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas expression of mRNA for m1 and m2 receptors was not found in the cells examined, such expression has been demonstrated in mononuclear cells. 36,52 The absence of receptor expression may reflect a true negative finding, or may result from low copy number transcripts that remain undetectable using the methods employed. However, given the sensitivity of RT-PCR analysis, one may question the functional relevance of seemingly absent, very low-density receptor sites.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the lymphocyte cholinergic system can take part in the regulation of the immune response [46] and inflammation, including the local release of mediators like NO and proinflammatory cytokines through the stimulation of muscarinic ACh receptors [47]. On the other hand, evidence also suggests that inflammation may be under neural control, also depending on cholinergic antiinflammatory mechanisms that inhibit the activation of macrophages and the release of cytokines [discussed in 48].…”
Section: Discussionmentioning
confidence: 99%
“…One possible role for G␣ o would be in signaling from GPCRs such as species of opioid, muscarinic acetylcholine (mAChR), and somatostatin receptors, which are expressed in the central nervous system, have been shown to use G␣ o (59 -61), and can be expressed by T cells (62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%